Sport-for-development interventions: whom do they reach and what is their potential for impact on physical and mental health in low-income countries? - Richards, J; Foster, C (Human Kinetics Publishers Inc., 2013)
Noncommunicable diseases and mental health are growing problems in low-income countries,1 and are of particular concern for urbanized and postconflict populations living in these settings.1,2 Physical activity interventions that are locally adapted and directed toward adolescents may be an effective approach to addressing these health problems during a critical life-stage transition.3,4 The sport-for-development sector claims to achieve this objective and has experienced rapid expansion in international investment since the UN International Year of Sport and Physical Education in 2005. However, there is a paucity of contextually relevant evidence supporting the positive rhetoric of sport-for-development advocates who often cite research from peaceful high-income countries to substantiate their claims of positive health impacts.5 In this commentary, we discuss the formative findings of a case-study evaluating a sport-for-development intervention in Gulu, Uganda. We explore who is actually reached by the intervention and the potential for impact on local physical and mental health needs. These are questions that sport-for-development organizations do not commonly address and the purpose of this commentary is to demonstrate the potential implications of these oversights.